Health planning in Malaysia: a case study of the National Strategic Plan Ending Aids 2016-2030 (NSPEA) - Wan, Arinah Deh Sze; Che Abdullah, Azreena; Esahak, Azreena; Nadzari, Ezy Eriyani; Nordin, Fairuz Nadiah; Subbarao, Gunenthira Rao; Zainal Abidin, Muhammad 'Adil; B. Z., Huda; I., Suriani (Community Health Society Malaysia (CHSM), 2016)
Introduction: Health planning is an essential part of healthcare system whereby policies will be translated into actions. There are many health planning theories that can be used which deal with the complexity of data and addressing the questions within the process. This paper reviewed the National Strategic Plan Ending AIDS 2016-2030 (NSPEA 2016-2030) which is one of the health planning in Malaysia.